2022
DOI: 10.3389/fimmu.2022.1085766
|View full text |Cite
|
Sign up to set email alerts
|

The role of lncRNAs in the tumor microenvironment and immunotherapy of melanoma

Abstract: Melanoma is one of the most lethal tumors with highly aggressive and metastatic properties. Although immunotherapy and targeted therapy have certain therapeutic effects in melanoma, a significant proportion of patients still have drug resistance after treatment. Recent studies have shown that long noncoding RNAs (lncRNAs) are widely recognized as regulatory factors in cancer. They can regulate numerous cellular processes, including cell proliferation, metastasis, epithelial-mesenchymal transition (EMT) progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…Recently, accumulating evidence has shown that lncRNAs play a key role in various biological processes in different malignancies, including melanoma. Evidence has demonstrated that lncRNAs can be used as a biomarker for the early diagnosis, prognosis and treatment of melanoma, based on their role 15–18 . In this systematic review and meta‐analysis, we aimed to summarize the results of individual studies on human samples and investigate the diagnostic and prognostic value of lncRNAs in melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, accumulating evidence has shown that lncRNAs play a key role in various biological processes in different malignancies, including melanoma. Evidence has demonstrated that lncRNAs can be used as a biomarker for the early diagnosis, prognosis and treatment of melanoma, based on their role 15–18 . In this systematic review and meta‐analysis, we aimed to summarize the results of individual studies on human samples and investigate the diagnostic and prognostic value of lncRNAs in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has demonstrated that lncRNAs can be used as a biomarker for the early diagnosis, prognosis and treatment of melanoma, based on their role. 15 , 16 , 17 , 18 In this systematic review and meta‐analysis, we aimed to summarize the results of individual studies on human samples and investigate the diagnostic and prognostic value of lncRNAs in melanoma. Our meta‐analysis showed a cumulative sensitivity of 0.724, a pooled specificity of 0.812 and an overall AUC of 0.837 for lncRNAs in diagnosing melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, significant progress has been made in advancing our understanding of the cutaneous melanoma tumor microenvironment (TME) ( Bagaev et al, 2021 ; Hodis et al, 2022 ; Zhou et al, 2022 ). This has resulted in increased illumination of the complex interplay between disease progression and inflammation ( Denk and Greten, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma is a highly aggressive skin cancer associated with a poor prognosis and a high metastatic rate, resulting in signi cant mortality each year [38,39]. Despite recent advances in treatment modalities such as surgery, radiotherapy, immunotherapy, and targeted therapy, the prognosis of patients with melanoma remains unfavorable [40]. Accumulating evidence supports the involvement of lncRNAs in melanoma initiation, development, and metastasis, as they in uence crucial cellular processes [41].…”
Section: Discussionmentioning
confidence: 99%